2021
DOI: 10.5606/tftrd.2021.6635
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mirror therapy on upper limb function, activities of daily living, and depression in post-stroke depression patients

Abstract: Objectives: This study aims to investigate the effects of mirror therapy (MT) on upper limb function, activities of daily living (ADLs), and depression in post-stroke depression patients. Patients and methods: Between November 2018 and December 2019, a total of 60 post-stroke patients (33 males, 27 females; mean age: 58.45±11.13 years; range, 35 to 88 years) were included. The patients were randomly divided into either the cosntrol group (n=30) or the MT group (n=30). Regular occupational therapy was provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, there are minor studies that assessed the effect of mirror intervention on a child"s psychological aspects. So, based on several studies that applied to post-stroke patients and have significant positive results in relieving psychological problems (Zhang et al, 2021;Polamraju, 2022). The current study was conducted to evaluate whether the mirror intervention is a feasible intervention for children with CP and may improve the children"s psychological aspects in the form of mastery motivation in performing tasks and daily activities independently as well as increasing their self-esteem and consequently promoting their positive self-concept.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Furthermore, there are minor studies that assessed the effect of mirror intervention on a child"s psychological aspects. So, based on several studies that applied to post-stroke patients and have significant positive results in relieving psychological problems (Zhang et al, 2021;Polamraju, 2022). The current study was conducted to evaluate whether the mirror intervention is a feasible intervention for children with CP and may improve the children"s psychological aspects in the form of mastery motivation in performing tasks and daily activities independently as well as increasing their self-esteem and consequently promoting their positive self-concept.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Recent studies report findings where OT is combined with other treatments, pharmacological and nonpharmacological, to evaluate the effectiveness of these ones. (Maltseva et al, 2018;Zhang et al, 2021). Most notably, the first study featured only men, whereas the other was specifically about mirror therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The pathogenesis of PSD involves various domains, including neurobiology, anatomy, psychology, sociology, and other domains, although the specific mechanisms are yet to be elucidated. Epidemiological surveys [2][3][4] reveal that the prevalence of PSD is approximately 31% within 5 years of the onset of stroke, with significant temporal variations peaking 3 to 6 months following the event. Additionally, 1 study found that the incidence of PSD was around 41.1% 3 months after the initial cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%